Flow cytometric assays for identity, safety and potency of cellular therapies. Issue 5 (21st September 2018) - Campbell, John D.M.; Fraser, Alasdair R.
Abstract : Cellular therapeutics are a fast‐growing, highly innovative area of medicine. This field encompasses well‐established immune therapies for infection and cancer, as well as newer cell therapies aimed at regenerating diseased tissue. Flow cytometry is arguably the most important tool in the development of advanced cellular therapeutics and plays a role in many aspects of manufacturing. Quality control of raw materials, assessing rates of cellular growth during complex in vitro culture processes, differentiation status, as well as final product characterization, viability, and product stability are all essential data to be collected and documented. This requires robust and validated flow cytometric analysis. In this review, we discuss flow cytometer set up; design and use of assays to maintain quality control in cell processing, and the building of a robust set of release criteria. The use of flow cytometric assays as surrogates of functional assays to allow comparison and release of cellular products for clinical use are reviewed with reference to monocyte‐derived and T cell products.